Individual Agency in Street-Level Bureaucrats' Implementation of Policy Reforms: The Role of Their Policy Evaluation and Self-efficacy. (27th January 2022) - Winter, Søren C; Mikkelsen, Maria Falk; Skov, Peter Rohde
Abstract: This paper develops and tests a parsimonious micro-theory of street-level bureaucrats' individual implementation behavior. By systemizing and synthesizing theoretical insights from Ajzen's theory of planned behavior, from Bandura's theory of perceived self-efficacy, and from implementation literature, we claim that street-level bureaucrats' policy implementation behavior is a function of their individual evaluation of the efficacy of the policy and of their own ability to implement the policy measures in terms of their perceived self-efficacy. We test our theory on a panel data set capturing teachers' implementation of the wide-scale Danish public school reform of 2014. We use administrative data and a five-wave panel survey (2014–18) of 2, 055 teachers in approx. 200 schools as well as their school leaders. Our results confirm the importance of teachers' perceived policy efficacy and of their perceived self-efficacy for their implementation behavior. When, as shown in this study, street-level bureaucrats' individual evaluations of a policy and their own perceived abilities shape their implementation behaviors, street-level bureaucrats become even more important individual policymakers than depicted in most research on street-level bureaucrats that mainly focuses on structural determinants of their behaviors rather than individual factors.